Pheromones that correlate with reproductive success in competitive conditions - Kenneth C. Luzynski (Nature Portfolio, 2021)
Abstract The major urinary proteins (MUPs) of house mice (Mus musculus) bind and stabilize the release of pheromones and other volatile organic compounds (VOCs) from urinary scent marks, which mediate chemical communication. Social status influences MUP and VOC excretion, and the urinary scent of dominant males is attractive to females. Urinary pheromones influence the sexual behavior and physiology of conspecifics, and yet it is not known whether they also affect reproductive success. We monitored the excretion of urinary protein and VOCs of wild-derived house mice living in large seminatural enclosures to compare the sexes and to test how these compounds correlate with reproductive success. Among males, urinary protein concentration and VOC expression correlated with reproductive success and social status. Territorial dominance also correlated with reproductive success in both sexes; but among females, no urinary compounds were found to correlate with social status or reproductive success. We found several differences in the urinary protein and volatile pheromones of mice in standard cages versus seminatural enclosures, which raises caveats for conventional laboratory studies. These findings provide novel evidence for chemical signals that correlate with male reproductive success of house mice living in competitive conditions.